Characteristic Features of Changes in Visual Fields in Patients with Brain Tumors (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Relevance of the problem.Due to a number of negative factors, both in nature in general and in the life of our society, the number of people who suffer from cancer of the central nervous system (CNS) is growing. These circumstances require constant attention to the development of the system for providing medical care to neurosurgical patients, as well as improving the methods of neurosurgical research in the patients being examined.